Manifestation du 17 octobre 1961 à Paris, L’oubli pour mémoire collective d’une violente répression policière - Julien Buzenet (Conserveries Mémorielles)
This article explores the processes of collective forgetting around the police repression of the October 17th 1961 demonstration in Paris during the Algerian war. In this article, the author treats oblivion as a form of memory. By addressing contextually the different elements involved in this lack of history, it exposes the censorship, amnesty, amnesia, silence and official or media discourses as limits to the social frameworks of the collective memory of this event and the violence it generated. Offering an anthropological analysis of the plurality of factors of this oversight, the author exhumes a hidden form of collective cooperation without which no scotoma could have been maintained permanently, and releases a field of unification between memory and history. Such collective amnesia is then revealed to be both incredibly composite by involving the political and the cognitive, the collective and the individual, while concerning everybody instead of being confined to national institutions. Conclusions are proposed on the memorial potential of oblivion as an unfinished conclusion constantly put into play.